TINJAUAN YURIDIS PERLINDUNGAN HUKUM TERHADAP HAK KORBAN ATAS TINDAK PIDANA PENGGELAPAN KENDARAAN BERMOTOR YANG DIGADAIKAN - Nasution, Ariqh Fahdi Anugrah; Saragih, Yasmirah Mandasari; ketaren, abdurahman Harits (Cattleya Darmaya Fortuna, 2025)
Casualties of pawned car theft are ensured by both criminal and respectful laws. The criminal component empowers casualties to get remuneration or the return of their automobiles whereas requiring the law to incur serious punishments on the guilty parties. In terms of the respectful component, casualties are entitled to sue for harms. In any case, victims find it challenging to realize their rights because lawful hone is regularly incapable. The court within the case ponder of choice No. 130/Pid.B/2024/PN Mdn was less resolved in maintaining the law against those who benefited from the benefits of wrongdoing and sentenced the casualty without taking into consideration their proprietorship rights to the pawned thing. Drawing from the already given background, this ponder recognizes a number of essential issues. The lawful rules relating to the wrongdoing of misappropriation of pawned engine vehicles are secured to begin with in this ponder. Based on the case consider of court choice No. 130/Pid.B/2024/PN.Mdn, the moment inquire about looks at the legitimate evaluation of assurance for the rights of victims of the wrongdoing of theft of pawned engine vehicles. With secondary data sources and essential legitimate materials within the frame of pertinent enactment reinforced by auxiliary legitimate materials within the frame of pertinent books and diaries, this think about utilizes a standardizing legitimate inquire about technique. This investigation appears that the judge blundered in imposing the defendant's discipline by coming up short to require into consideration the rights of casualties who have maintained critical misfortunes. Concurring to Law No. 13 of 2006's Article 7 on the Protection of Witnesses and Casualties, casualties of violations have a right to state recompense. Judges must too penalize guilty parties who pick up commodities from violations in line with Article 480 of the Criminal Code, which stipulates that everybody who knows or ought to accept that the things are gotten from a wrongdoing faces a most extreme imprison sentence of four a long time. It is accepted that taking this under consideration will have a hindering impact on those who commit wrongdoings and those who advantage from them.